Four In A Row / Vier Op Een Rij - Professor Puzzle (Dublin : Professor Puzzle, 2021)
Houten versie van het klassieke spel Vier Op Een Rij. Lukt het jou om als eerste een serie van vier te maken?
Wooden version of the classic game Four in a Row. Can you be the first to make a series of four?
Keywords: Strategie; Gezelschapsspellen